2020
DOI: 10.1007/s12015-020-10033-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of Trials Currently Testing Stem Cells for Treatment of Respiratory Diseases: Facts Known to Date and Possible Applications to COVID-19

Abstract: Therapeutic clinical and preclinical studies using cultured cells are on the rise, especially now that the World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) a "public health emergency of international concern", in January, 2020. Thus, this study aims to review the outcomes of ongoing clinical studies on stem cells in Severe Acute Respiratory Syndrome (SARS), Acute Respiratory Distress Syndrome (ARDS), and Middle East Respiratory Syndrome (MERS). The results will be associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 107 publications
(132 reference statements)
1
14
0
Order By: Relevance
“…It is well known that stem cells have the potential to differentiate into lung cells among others, reprogramming the immune response to reduce destructive inflammatory elements and directly replace damaged cells and tissues. (9) Furthermore, the growth factor cocktail has apocrine effects on the modulation of the cytokine storm, not only in the lungs but throughout the circulatory system, explaining this phenomenon found in our study, which was evidenced by a decrease in acute phase reactants. It is almost certain that if we had the chance to treat those patients earlier, we would be able to avoid the AKI and hemodialysis requirement, since the immunomodulation with the therapy would suppress the cytokine storm.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It is well known that stem cells have the potential to differentiate into lung cells among others, reprogramming the immune response to reduce destructive inflammatory elements and directly replace damaged cells and tissues. (9) Furthermore, the growth factor cocktail has apocrine effects on the modulation of the cytokine storm, not only in the lungs but throughout the circulatory system, explaining this phenomenon found in our study, which was evidenced by a decrease in acute phase reactants. It is almost certain that if we had the chance to treat those patients earlier, we would be able to avoid the AKI and hemodialysis requirement, since the immunomodulation with the therapy would suppress the cytokine storm.…”
Section: Discussionsupporting
confidence: 72%
“…The lower incidence of sepsis in group A can be explained by this phenomenon, since the shorter hospital stay is a protective factor against nosocomial infections,(23) and it was found that around 3 patients are required to be treated to have this protective effect with the stem cell nebulization (NNT=2.5). An attenuation of bacterial sepsis mediated by stem cells had been described, via several mechanisms, such as improving the phagocytic ability, secreting anti-microbial peptides,(9,24) and increasing bacterial clearance. (9,25)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the immunomodulatory potential of the stem cells in sepsis and clinical evolution of chronic conditions with the stimulation by humoral factors, strategies such as stem cell-based therapy are being proposed to regulate inflammation, prevent or mitigate this cytokine storm through their immunomodulatory capacity. 5…”
Section: Introductionmentioning
confidence: 99%